2011
DOI: 10.1093/sleep/34.3.341
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine Transporter is Decreased in the Striatum of Subjects with Restless Legs Syndrome

Abstract: The current study found a significant decrease in DAT BP in two independent studies. These results when viewed along with prior RLS SPECT and autopsy studies of DAT, and cell culture studies with iron deficiency and DAT, suggest that membrane-bound striatal DAT, but not total cellular DAT, may be decreased in RLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(73 citation statements)
references
References 42 publications
3
64
0
2
Order By: Relevance
“…Given that nigrostriatal dopaminergic dysfunction has been implicated in the pathophysiology of idiopathic RLS and idiopathic RBD, several authors have postulated that both sleep complaints might be related to nigrostriatal dopaminergic dysfunction also in MJD [20][21][22]. Furthermore, there are clinical, imaging and anatomopathological evidence that basal ganglia and substantia nigra degeneration may occur in MJD patients [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Given that nigrostriatal dopaminergic dysfunction has been implicated in the pathophysiology of idiopathic RLS and idiopathic RBD, several authors have postulated that both sleep complaints might be related to nigrostriatal dopaminergic dysfunction also in MJD [20][21][22]. Furthermore, there are clinical, imaging and anatomopathological evidence that basal ganglia and substantia nigra degeneration may occur in MJD patients [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] Worsening in afternoon or at night Yes [1,15,16] Yes [6] Urge to move Overwhelming desire to keep sucking the teeth [15] parafunctional habits [15,18] Present [6] Relieving factors Eating [1,10,15,16]. Movement of the tongue [19] Moving the limbs [ [37,38] nerves, like BMS) may have an important role in the pathogenesis of RLS [27,28]. Jääskeläinen [4] suggests that 20-40% patients with BMS may have predominantly involvement of central dopaminergic dysfunction (the main proposed pathophysiology of RLS).…”
Section: Rls With Bms: Any Correlation?mentioning
confidence: 99%
“…However, unlike RBD, there is no evidence suggesting RLS as a risk factor of PD, and the co-morbidity of RLS in PD patients varies widely from 0 to 50% [119]. In contrast to PD, which shows degeneration of the striatonigral dopaminergic neurons, confirmed by the reduced striatal uptake observed in neuroimaging studies, in idiopathic RLS, PET/SPECT studies have not produced consistent findings of striatonigral dopaminergic dysfunction [120,121]. Postmortem studies of RLS patients have found an increased total and phosphorylated tyrosine hydroxylase in the putamen and substantia nigra [122].…”
Section: Restless Leg Syndromementioning
confidence: 98%